Experimental Study of the Refractive Index Sensitivity in Arc-induced Long Period Gratings - Flavio Esposito; Rajeev Ranjan; Stefania Campopiano; Agostino Iadicicco (IEEE Photonics Journal, 2017)
This paper presents an experimental study of the sensitivity characteristics to the surrounding refractive index (SRI) in arc-induced long period gratings (LPGs), in order to outline their dependence over the fabrication parameters. Several LPGs were fabricated, with spectral features that are appealing for chemical sensing applications, e.g., negligible power losses, bands depth greater than 20 dB, and total length smaller than 35 mm. In addition, low spatial periods Λ, which are close to the limit of the arc-based fabrication technique, were selected in order to excite high-order cladding modes. In particular, the period was chosen in range 350–500 μm to focus attention on the same cladding modes for the gratings under investigation. Accordingly, a wide experimental analysis was then carried out to investigate the dependence of the sensitivity to SRI changes on the period in order to derive design criteria for LPG fabrication. In the wavelength range 1100–1700 nm and taking into consideration the attenuation bands related to the LP05 and LP06 cladding modes, an SRI sensitivity enhancement up to one order of magnitude can be achieved by proper selection of the grating period.